1973
DOI: 10.1128/aac.3.5.625
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of R931 and Other Pseudomonas aeruginosa R Factors

Abstract: R factors were detected in 3.3% of 233 hospital isolates of Pseudomonas aeruginosa using P. aeruginosa recipients in conjugations. Transferred markers included streptomycin, tetracycline, and sulfonamide resistance. Gentamicin resistance was transferred from two strains previously shown to acetylate gentamicin. A group of R factors exemplified by R931 were characterized by failure to transfer to Escherichia coli recipients. Such R factors formed a single compatibility group when examined in a P. aeruginosa rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Results of incompatibility studies reported here assigned R772 to the P-1 group (Stanisich, 1974;Bradley & Rutherford, 1975;Shahrabadi et al, 1975;Bryan et al, 1973;Jacoby, 1974; although its incompatibility interactions with R751 are llot typical of members of this group. Plasmids RP4, R702 or R1033, for example, interact reciprocally with R751, eliminating and being eliminated by it Smith et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Results of incompatibility studies reported here assigned R772 to the P-1 group (Stanisich, 1974;Bradley & Rutherford, 1975;Shahrabadi et al, 1975;Bryan et al, 1973;Jacoby, 1974; although its incompatibility interactions with R751 are llot typical of members of this group. Plasmids RP4, R702 or R1033, for example, interact reciprocally with R751, eliminating and being eliminated by it Smith et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The R factor 931 is an example of a group of R factors detected in strains of Pseudomonas aeruginosa, which are unusual in that they fail to transfer to Escherichia coli or Proteus mirabilis but act as a naturally occurring, high-frequency transfer system when P. aeruginosa recipients are used in mating (4). Thus R931 appears to be of unique origin relative to previously studied R factors.…”
mentioning
confidence: 99%
“…The characteristics of R factors carried by clinical strains of Pseudomonas aeruginosa isolated from different geographical areas have been described by a number of investigators (Datta et al 1971 ;Stanisich & Holloway, 1971 ;Chabbert et al 1972;Grinsted et al 1972;Ingram et al 1972;Kawakami et al 1972;Bryan et al 1973;Ingram, 1973;Morgan, Saunders, Stanisich & Richmond, 1973;Olsen & Shipley, 1973;Chandler & Krishnapillai, 1974a, b ;Stanisich, 1974). One of these strains, P .…”
Section: Introductionmentioning
confidence: 99%